Development of Android-Based Educational Games to Improve Students’ Learning Outcomes in Hydrocarbon - Putri, Isma Yanti Vitarisma Sukirno; Joharmawan, Ridwan; Munzil, Munzil; Vaudhi, Fasril (Jurnal Pendidikan MIPA, 2023)
Android-based educational game is a game using a smartphone operating system with certain teaching materials as learning media in an interesting, unique, and fun. The purpose of this study was to produce educational game media product that are feasible and valid. This development research used the ADDIE model (analyze, design, developt, implementation, and evaluation). The results of the study: (1) the media expert's validity value was 96.6% in the very feasible and very valid category, (2) the material expert's validity value was 91.4% in the very feasible and very valid category, and (3) the results of the students' readability test was 93.6% in the very feasible and very valid category, (4) N-Gain score of 0.84 in the high category and an effectiveness level of 84.6% in the "effective" category. Therefore, the android-based educational game media was effectively used to improve student learning outcomes with high effectiveness. Keywords: educational game, chemistry learning, ADDIE.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp14-27